Rio de Janeiro e a Avenida Beira Mar: desejo de paisagem e cidade balneário nas primeiras décadas do século XX - Rafael Winter Ribeiro (Confins)
The urban interventions which began during the administration of Mayor Pereira Passos (1902-1906) are commonly pointed out as a milestone in the construction of modernity in Rio de Janeiro. One of the main works was the construction of Beira Mar Avenue, a large boulevard linking the Center to the South Zone, along the edge of Guanabara Bay, an area that was consolidated as a vector of occupation of a more affluent population. In its configuration, it offered great visibility to two elements that were consecrated as defining the carioca landscape, the sea and the mountain, putting in evidence the desire to use it. In the same period, the city experienced a considerable growth of activities linked to baths, as a seaside city, that found place in the new avenue. The need for contact with open spaces and nature caused a massive exposure of this landscape that was unfolding from these new points of view. How is Beira Mar Avenue related to the process of construction of the Rio de Janeiro landscape? What is the role of seaside practices? Which seaside structures and practices participated in this process and how? These are some of the questions that guide this article. The paper points out how the construction of an infrastructure linked to the ideal of a seaside city on the Avenida Beira Mar corroborates this relationship. Hotels, casinos, sea baths, sports, walks and parties contribute to forge this association between a seaside city and the consolidation of Rio’s landscape.